Do adult eastern bluebird Sialia sialis males recognize juvenile-specific traits? - LIGON, RUSSELL A. (2009)
Juveniles of many avian species possess spotted or mottled plumage that is distinct from the plumage of adults. Such plumage has typically been assumed to aid in camouflaging vulnerable immature birds. Here, we propose that spotty plumage signals juvenile status, thereby decreasing aggression from territorial adults. We tested this hypothesis by measuring the aggressive responses of adult eastern bluebird males to different combinations of simultaneously presented taxidermic mounts. We found that territorial males attacked adult models significantly more than juvenile models, and that they attacked adult models with orange breasts (typical of adults) more frequently than they attacked adult models with spotty breasts (typical of juveniles). We found no difference in attack rates when models with white breasts (a novel trait) were presented with models possessing spotty breasts. These observations indicate that breast colour is a cue used by territorial adults when identifying conspecific intruders, but that adults do not recognize juvenile-specific plumage as such. Adults respond aggressively only to orange-breasted intruders.